Tinjauan Etis Kristiani terhadap Putusan MA (tentang Usia Cawagub, Cawalkot, dan Cabup) - Sanjaya, Frengky (Lembaga Teewan Journal Solutions, 2026)
The Supreme Court Decision Number 23 P/HUM/2024, which modified the age requirements for regional head candidates during the 2024 local election stages, has sparked ethical debates from a Christian ethical perspective. This study employs a descriptive qualitative method with a literature study approach. The findings indicate that the sudden regulatory change potentially violates the principles of justice, truth, and propriety in Christian ethics. The analysis draws on multiple disciplines, including philosophical ethics, legal science, political science, social psychology, economics, and theology. To address these ethical concerns, the researcher recommends postponing the implementation of the decision, establishing an independent panel, and reviewing the Supreme Court ruling with public input. Relevant stakeholders are expected to demonstrate critical thinking, transparency, principled commitment, and humility. Christian values—such as upholding truth and justice, avoiding conflicts of interest, and maintaining integrity and consistency—must be actualized in resolving this issue to strengthen democratic processes and preserve public trust in the judiciary